Plant tolerance to excess light energy and photooxidative damage relies on plastoquinone biosynthesis - Ksas, Brigitte (Sci Rep, 2015)
Plastoquinone-9 is known as a photosynthetic electron carrier to which has also been attributed a role in the regulation of gene expression and enzyme activities via its redox state. Here, we show that it acts also as an antioxidant in plant leaves, playing a central photoprotective role. When Arabidopsis plants were suddenly exposed to excess light energy, a rapid consumption of plastoquinone-9 occurred, followed by a progressive increase in concentration during the acclimation phase. By overexpressing the plastoquinone-9 biosynthesis gene SPS1 (SOLANESYL DIPHOSPHATE SYNTHASE 1) in Arabidopsis, we succeeded in generating plants that specifically accumulate plastoquinone-9 and its derivative plastochromanol-8. The SPS1-overexpressing lines were much more resistant to photooxidative stress than the wild type, showing marked decreases in leaf bleaching, lipid peroxidation and PSII photoinhibition under excess light. Comparison of the SPS1 overexpressors with other prenyl quinone mutants indicated that the enhanced phototolerance of the former plants is directly related to their increased capacities for plastoquinone-9 biosynthesis.